The Unanimity Rule and Extremely Asymmetric Committees - Ruth Ben-Yashar; Leif Danziger (Institute for the Study of Labor (IZA), 2016)
This paper analyzes how to allocate experts into committees that use the unanimity rule to make decisions. We show that an optimal allocation of experts is extremely asymmetric. To reach the optimal allocation, therefore, one needs only to rank the experts in terms of their abilities and then allocate adjacent experts such that an expert's ability tends to vary inversely with the size of his committee. In the special case of three-member committees, we show that the optimal allocation maximizes the sum of the products of the experts' skills in each committee.
Keywords: D71; 330; unanimity rule; extremely asymmetric committees; optimal composition of committees